Comparison of two training programmes on paramedic-delivered CPR performance. Issue 5 (23rd December 2015) - Govender, Kevin; Sliwa, Karen; Wallis, Lee; Pillay, Yugan
Abstract : Objective: To compare CPR performance in two groups of paramedics who received CPR training from two different CPR training programmes. Methods: Conducted in June 2014 at the Hamad Medical Corporation Ambulance Service, the national ambulance service of the State of Qatar, the CPR performances of 149 new paramedic recruits were evaluated after they had received training from either a traditional CPR programme or a tailored CPR programme. Both programmes taught the same content but differed in the way in which this content was delivered to learners. Exclusive to the tailored programme was mandatory precourse work, continuous assessments, a locally developed CPR instructional video and pedagogical activities tailored to the background education and learner style preferences of paramedics. At the end of each respective training programme, a single examiner who was blinded to the type of training paramedics had received, rated them as competent or non-competent on basic life support skills, condition specific skills, specific overall skills and non-technical skills during a simulated out-of-hospital cardiac arrest (OHCA) assessment. Results: Paramedics who received CPR training with the tailored programme were rated competent 70.9% of the time, compared with paramedics who attended the traditional programme and who achieved this rating 7.9% of the time (p<0.001). Specific improvements were seen in the time required to detect cardiac arrest, chest compression quality, and time to first monitored rhythm and delivered shock. Conclusions: In an OHCA scenario, CPR performance rated as competent was significantly higher when training was received using a tailored CPR programme.